Densification of graphite under high pressure and moderate temperature. (March 2020) - Aguiar, Jeffery A.; Kwon, Seongtae; Coryell, Benjamin D.; Eyerman, Eric; Bokov, Arseniy A.; Castro, Ricardo H.R.; Burns, Douglas; Hartmann, Howard T.; Luther, Erik P.
Graphical abstract: Highlights: Graphite specimens were successfully sintered with spark plasma sintering under moderate temperatures and pressures. Materials are pressed and sintered to over 2.0 g/cm 3 with no visible defects. Sintering graphite under the conditions reported represents a significant achievement. Abstract: From serving as the primary host material from near-ideal neutron moderators to high-capacity discharge electrodes, graphite is a ubiquitous material for a number of advanced applications. The focus of this work, however, is on those applications requiring high-purity fine-grained densified graphite monoliths fabricated to scale with minimal effort. To date, graphite monoliths have been constrained to lower final part densities and purities due to the technical challenges associated with mainly hot pressing and extrusion, that ultimate limit these attributes. In this study, we report on the use of spark plasma sintering as an alternate method for fabrication at temperatures below 1, 200 °C and less than 300 MPa without the use of binders, additional resins, or post-thermal treatments. Formed part sizes from few to several millimeters in size, we report highly dense (2.095 g/cm 3 ), well-bonded, and low-defect-ridden graphite with uniform composition examined by detailed X-ray and electron-based microscopy. The results are an initial report on the use this technique to sinter graphite under moderate conditions that may support small to moderate-scale technical production needs that require low-cost, high-purity, and high-density graphite.